Historical Counter-Narratives: Japanese Christians’ Advocacy for South Korean Atomic Bomb Victims - Duró, Ágota (Japanese journal of religious studies, 2020)
This article delineates the process that Japanese adherents of Christianity, despite Japan being one of the least Christian nations in the world, were at the forefront of civil society movements in the early 1970s to advocate for the rights of atomic bomb survivors who returned to South Korea after 1945. Many Christians, when considering Japan’s accountability in World War II, were driven by contrition and a strong sense of righteousness, and they considered reconciliation with other Asian nations of the utmost importance. This article explores the support activities of three Christians who were prominent members of grassroots movements that emerged in the 1970s to assist Korean survivors in various parts of Japan. Despite belonging to diverse Protestant denominations, the advocates were motivated to act by similar Christian ethics: to stand up for the oppressed, consolidate peace, love their neighbors, and demand social justice. Their example illustrates the larger historical process of Christian reassessment of their prewar morals in a way that facilitated their emergence as the preeminent promoters of pacifism and antiwar activism in the postwar era.